2020
DOI: 10.1055/a-1229-8393
|View full text |Cite
|
Sign up to set email alerts
|

Einfluss der thermischen Enthornung mit unterschiedlichem Schmerzmanagement auf die Gesundheit von Kälbern

Abstract: Zusammenfassung Gegenstand und Ziel Die thermische Enthornung von Kälbern stellt einen mit Schmerz und Stress verbundenen Eingriff dar. Verschiedene Verfahren der Schmerzausschaltung sowie die unmittelbaren Auswirkungen auf physiologische, biochemische und ethologische Prozesse wurden bereits ermittelt. Ziel der Studie war zu evaluieren, ob die Enthornung selbst, das Schmerzmanagement oder das Alter der Kälber zum Zeitpunkt des Eingriffs die Gesundheit der Tiere beeinflusst. Material und Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The following clinical complexes were generated for statistical analysis: rectal body temperature, respiratory, circulatory, and digestive system, ketonuria [evaluated by detection of acetoacetic acid in urine samples (Ketostix, Bayer Vital GmbH), for sample collection time points, see next section], udder, genital tract (calving ease, calving injuries, retained placenta, metritis, endometritis), locomotion apparatus, claws, skin, lymph nodes, blood sampling (jugular vein) and biopsy site, and treatments [antibiotics, nonsteroidal anti-inflammatory drugs, gynecological medication and other treatments (e.g., other drugs, surgery)]. The clinical findings were assigned to the different complexes and evaluated using a scoring system (one score per complex and animal for the trials period) for general examination for different organ systems: 0 = no abnormality observed; 1 = abnormality observed once, but evaluated as not requiring treatment; 2 = abnormality observed more than once throughout the trial, but evaluated as not requiring treatment; 3 = abnormality entailed treatment (similar to Kretschmann et al, 2020); displaced abomasum: yes/no; treatments: 0 = no, 1 = yes, once/one, 2 = yes, several treatments; clinical ketosis: yes/no; calving ease: 1 = easy, 2 = medium, 3 = heavy. The clinical scores were evaluated per trait and as total sum (the higher the sum, the more the animal was clinically affected).…”
Section: Production and Clinical Traitsmentioning
confidence: 99%
“…The following clinical complexes were generated for statistical analysis: rectal body temperature, respiratory, circulatory, and digestive system, ketonuria [evaluated by detection of acetoacetic acid in urine samples (Ketostix, Bayer Vital GmbH), for sample collection time points, see next section], udder, genital tract (calving ease, calving injuries, retained placenta, metritis, endometritis), locomotion apparatus, claws, skin, lymph nodes, blood sampling (jugular vein) and biopsy site, and treatments [antibiotics, nonsteroidal anti-inflammatory drugs, gynecological medication and other treatments (e.g., other drugs, surgery)]. The clinical findings were assigned to the different complexes and evaluated using a scoring system (one score per complex and animal for the trials period) for general examination for different organ systems: 0 = no abnormality observed; 1 = abnormality observed once, but evaluated as not requiring treatment; 2 = abnormality observed more than once throughout the trial, but evaluated as not requiring treatment; 3 = abnormality entailed treatment (similar to Kretschmann et al, 2020); displaced abomasum: yes/no; treatments: 0 = no, 1 = yes, once/one, 2 = yes, several treatments; clinical ketosis: yes/no; calving ease: 1 = easy, 2 = medium, 3 = heavy. The clinical scores were evaluated per trait and as total sum (the higher the sum, the more the animal was clinically affected).…”
Section: Production and Clinical Traitsmentioning
confidence: 99%
“…Therefore, aside from important and well-acknowledged animal welfare concerns, different zootechnical procedures in animal production, inflicting short-term stress due to handling and restraint, may have an influence on animal productivity (Johnson and Vanjonack, 1976;Miranda-de la Lama et al, 2011Marco-Ramell et al, 2016;Grandin, 2021). For these reasons, different protocols to reduce pain and stress in the animal have been developed since studies have shown not only a benefit in this respect, but also in the later animal health status (Ting et al, 2003;Kretschmann et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Addition of an NSAID administered preemptively may have prevented the peri -and postoperative stress response in the study sheep. The positive effect of a multimodal pain management protocol including an NSAID on postoperative well-being has already been investigated in other procedures (Dinniss et al, 1997;Graham et al, 1997;Paull et al, 2007) and animal species (Banse and Cribb, 2017;Fekry et al, 2019;Kretschmann et al, 2020;Stilwell et al, 2020). Until now, there have been no studies analyzing the effect of a multimodal pain management protocol that incorporates an NSAID on claw treatment in sheep (PubMed search November 28, 2022, search terms sheep, multimodal pain management, antiphlogistic, claw treatment).…”
Section: Limitations Of the Studymentioning
confidence: 99%